Le traitement du genre dans les publicités télévisuelles pour enfants - Antoine Radel; Gérard Neyrand (Communication)
Discursive strategies in television programming play a role in structuring young children’s relationship to the world. The authors studied a selected sample of advertising spots broadcast during the weekend morning French television programs intended for children. A particular attention is paid to the narratives favouring the dissemination of extremely stereotypical, gendered norms of behaviour that strongly shape children’s acceptance of gendered roles.